2018
DOI: 10.31106/jema.v15i2.1125
|View full text |Cite
|
Sign up to set email alerts
|

Social Commerce Adoption in SME’s

Abstract: Small and medium enterprises (SME's) has gradually become an economic backbone for several developing country including Indonesia. In several studies, it was assumed that SME's was a sign of self-sufficiency concept. In the economic strike, SME's could sustain the price of several staple goods that are related to society livelihoods such as food and attire. South Kalimantan Province was well known for its authentic fabric namely sasirangan produced by local SME's spread all around the area. SME's are nowadays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Whereas UTAUT has facilitating conditions, effort expectancy, habit, hedonic, and trust (Abed et al, 2015;Bamansoor et al, 2020;Ben et al, 2018;Dahnil et al, 2014;Gatautis & Medziausiene, 2014;Zamrudi & Wicaksono, 2018). Table 2 shows a summary of Related Work by Prior Research.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas UTAUT has facilitating conditions, effort expectancy, habit, hedonic, and trust (Abed et al, 2015;Bamansoor et al, 2020;Ben et al, 2018;Dahnil et al, 2014;Gatautis & Medziausiene, 2014;Zamrudi & Wicaksono, 2018). Table 2 shows a summary of Related Work by Prior Research.…”
Section: Related Workmentioning
confidence: 99%
“…Trust, perceived usefulness and information quality 14. Zamrudi & Wicaksono (2018) This study aims to investigate the attitude of SMEs in the use of S-Commerce in the province of South Kalimantan, Indonesia.…”
Section: Tam Delonementioning
confidence: 99%
See 1 more Smart Citation
“…The SME's success story shows that there is a great effort in maintaining the SME's performance both of the entrepreneur side and from government support. The arise of information and technology also becoming an essential factor to sustain the SME's business (Zamrudi & Wicaksono, 2018). Prior studies also demonstrated that the success of SME's has a direct impact on the development of economic growth both in developed and developing countries (Demirbag, Tatoglu, Tekinkus, & Zaim, 2006).…”
Section: Introductionmentioning
confidence: 99%